Fiscal policy and structural transformation in developing economies - Peter Skott (University of Massachusetts, Department of Economics, 2020)
Developing economies with high levels of open or hidden unemployment face structural transformation problems. Unlike in mature economies there are no structural aggregate demand problems, and sustained aggregate demand stimulus can lead to a profit squeeze in the modern sector and deindustrialization. Adaptations of functional finance to developing economies should aim to stabilize the level and composition of demand at values that are consistent with a target rate of growth of the modern sector. Populist temptations, however, may lead to deindustrialization.
Keywords: E62; O11; O23; 330; Sectoral transformation; Dutch disease; functional finance